2022
DOI: 10.1155/2022/5952296
|View full text |Cite
|
Sign up to set email alerts
|

Application Values of 2D and 3D Radiomics Models Based on CT Plain Scan in Differentiating Benign from Malignant Ovarian Tumors

Abstract: Background. Accurate identification of ovarian tumors as benign or malignant is highly crucial. Radiomics is a new branch of imaging that has emerged in recent years to replace the traditional naked eye qualitative diagnosis. Objective. This study is aimed at exploring the difference in the application potential of two- (2D) and three-dimensional (3D) radiomics models based on CT plain scan in differentiating benign from malignant ovarian tumors. Method. A retrospective analysis was performed on 140 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“… Incomplete ultrasound, MRI, or pathological data; combined with severe organic diseases, such as coagulation dysfunction, renal insufficiency, heart failure, and other surgical contraindications; history of ovarian surgery; combined with other pelvic diseases, such as endometrial cancer and rectal cancer. 207 NR Li et al, 34 2022 a Patients with ovarian tumor confirmed by histopathology; no history of malignant tumors other than ovarian tumor; patients who were undergoing pelvic CT examination within half a month before surgery. Those who had received radiotherapy, chemotherapy, or radiotherapy–chemotherapy before CT examination; patients diagnosed with inflammatory diseases; patients with low image quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Incomplete ultrasound, MRI, or pathological data; combined with severe organic diseases, such as coagulation dysfunction, renal insufficiency, heart failure, and other surgical contraindications; history of ovarian surgery; combined with other pelvic diseases, such as endometrial cancer and rectal cancer. 207 NR Li et al, 34 2022 a Patients with ovarian tumor confirmed by histopathology; no history of malignant tumors other than ovarian tumor; patients who were undergoing pelvic CT examination within half a month before surgery. Those who had received radiotherapy, chemotherapy, or radiotherapy–chemotherapy before CT examination; patients diagnosed with inflammatory diseases; patients with low image quality.…”
Section: Resultsmentioning
confidence: 99%
“… 3663/100 2015.01–2020.12 No Guo et al, 33 2022 a Retrospective study, data from Qilu Hospital. 138/69 2018.04–2021.04 No Li et al, 34 2022 a Retrospective study, data from the First Affiliated Hospital of Nanchang Medical College. 99/41 2017–2020 No Wang et al, 35 2021 a Retrospective study, data from Tianjin Medical University Cancer Institute and Hospital.…”
Section: Resultsmentioning
confidence: 99%
“…All images were saved as Digital Imaging and Communications in Medicine (DICOM) and imported into the ITK-SNAP software (version 3.8.0, http://www.itksnap.org ) for segmentation. Some studies have shown that one slice (2D) with the largest cross-section of the tumor and the entire tumor volume (3D) for segmentation has comparable diagnostic performance, and there are also some studies that use one slice for tumor segmentation ( 17 20 ). So, in this study, the regions of interest (ROIs) were manually segmented ( Figure 2 ) on the axial slice with the largest cross-section of the tumors on T2w, T2 FLAIR, and T1c images by two authors (S Wu and P He, with 4 and 6 years of diagnostic experience in neuroradiology, respectively) who were blinded to histological results.…”
Section: Methodsmentioning
confidence: 99%
“…32 In recent years, a number of CT radiomics studies were conducted to predict the clinicopathological characteristics of ovarian tumors, including discriminating malignant from borderline or benign ovarian masses, differentiating primary and secondary EOC, as well as predicting nodal or abdominopelvic metastases in ovarian cancer. [33][34][35][36][37] Histologic subtype is an important tumor characteristic that affects clinical management of EOC. Excellent performance of CT radiomics was found in our multicenter study.…”
Section: Jama Network Open | Obstetrics and Gynecologymentioning
confidence: 99%